The articulation of the steam methodology with integrative technologies as possibilities of use in hybrid teaching - Xavier Guterres, Lisandra; Gonzaga Guarenti , Rosiméri; Oxlei de Souza Ortiz, José; Alberto Guarenti, Carlos; Bederode, Igor; Otoni Meireles Ribeiro, Luis (Seven Editora, 2023)
The articulation of steam methodology with integrative technology as possibilities for use in hybrid teaching. The Covid-19 pandemic imposed the need to use new strategies to continue educational actions. Therefore, it became important to think about teach- ing methods in which face-to-face and online activities are interspersed, such as Hybrid Teaching. Therefore, this research aims to present proposals for using the STEAM methodology with the resources and technologies available to students, combined with active integrative methodologies. This article was structured through empirical bibliographical research in which educational robotics, virtual and augmented reality, and gamification as integrative technologies that can be used through project-based learning in the context of face-to-face and remote teaching are analyzed. DOI: https://doi.org/10.56238/devopinterscie-175